A COMPARATIVE ANALYSIS BETWEEN NON-MESH (BASSINI'S) AND MESH (LICHTENSTEIN) REPAIR OF PRIMARY INGUINAL HERNIA - Malik, Arshad M; Khan, Asad; Jawaid, Atif; Laghari, Abdul Aziz; Talpur, K. Altaf Hussain (Journal of Ayub Medical College Abbottabad, 2009)
Background: The groin hernia repair is one of the common operations in general surgery. The optimum repair method is under debate and the best mode of repair is yet to be decided. This study is conducted to compare the results of open non-mesh (Modified Bassini's) and Lichtenstein's mesh repair of primary inguinal hernia in terms of recurrence, postoperative complications and quality of life in the long term. Methods: This retrospective comparative analytical study includes 840 patients of which 40 patients were excluded from the study due to various reasons. The remaining 800 patients with unilateral primary inguinal hernia, above 16 years of age, operated during January 2000 to December 2007 in a teaching hospital are included in the study. Of the total number, 392 patients (49%) underwent Lichtenstein mesh repair, while remaining 408 patients (51%) were operated by modified Bassini's suture technique. Follow up was conducted 1, 5, 8 and 15 days; 1, 2, 6, 24 and 36 months. Results: The recurrence rate and postoperative pain were significantly low in Lichtenstein mesh repair compared to open non-mesh repair by modified Bassini's technique (p<0.001). Recurrence occurred in 8 (2.0%) out of 392 patients those with Lichtenstein mesh repair. On the other hand 29 (7.1%) patients with Bassini's repair reported recurrence within 3 years time. Conclusion: Mesh repair of inguinal hernia is much superior to non-mesh repair in terms of recurrence and postoperative chronic pain. Keywords: Inguinal hernia, open repair, Lichtenstein repair, morbidity, recurrence